Problems of language skills development in grade 4 elementary schools - Triastuti, Atikah; Wiarsih, Cicih (PT The Collaboration UVW, 2023)
Developing language skills in fourth-grade elementary school poses a complex problem due to factors such as teacher quality, teaching methods, and the curriculum used. A literature study was conducted to identify the problems related to language skill development in fourth-grade elementary schools and find solutions. This literature study used a qualitative descriptive approach and collected data from various relevant journals. Based on literature analysis, it was found that the main problem in developing language skills in fourth-grade elementary school was the lack of varied teaching methods implemented by teachers and limited resources for language skill development, as well as the need for better government and parental support to improve students’ language abilities. To address these problems, several solutions are suggested, such as training to improve teacher quality, using varied teaching methods, and campaigns aimed at increasing awareness and participation of parents and the government in supporting children’s language skills.